We Heal as One: Interprofessional Health Collaboration During the Covid-19 Pandemic - Bathan, Trisha M.; Delos Santos, Aldous N.; Gealone, Regine G.; Laja, Aezle F.; Magauay, Rosejane M.; Piodos, Doz M.; Ramirez, Riel Mari L.; Ramos, Rahya D.; Tamano, Jonel M.; Felicen, Gerald; Sibayan, Maria Julita SJ. (8ISC Proceedings: Covid-19; 8ISC Proceedings: Covid-19, 2022)
A collaborative healthcare system enabled through multi-professional and interprofessional partnerships that pave the way to improved health outcomes has been the director of the Millennium Development Goals (World Health Organization, 2016). But the occurrence of the global COVID-19 pandemic challenged the healthcare system in unprecedented ways. This study explored the essence of interprofessional collaboration among medical and paramedical healthcare professionals. A phenomenological research study through photovoice was employed and analyzed using thematic analysis. Study corpus was gathered from a total of 15 participants, including three medical technologists, three nutritionists and dieticians, three radiologic technologists, three pharmacists, two nurses, and one physician. Four themes surfaced from the responses, namely: unity in diversity, paradigm shift, parallel dilemmas, and resilient optimism. Keywords : healthcare system, interprofessional collaboration, medical, healthcare